Mobile Robot Navigation Based on Embedded Computer Vision - Alberto Marroquín; Gonzalo Garcia; Ernesto Fabregas; Ernesto Aranda-Escolástico; Gonzalo Farias (Mathematics, 2023)
The current computational advance allows the development of technological solutions using tools, such as mobile robots and programmable electronic systems. We present a design that integrates the Khepera IV mobile robot with an NVIDIA Jetson Xavier NX board. This system executes an algorithm for navigation control based on computer vision and the use of a model for object detection. Among the functionalities that this integration adds to the Khepera IV in generating guided driving are trajectory tracking for safe navigation and the detection of traffic signs for decision-making. We built a robotic platform to test the system in real time. We also compared it with a digital model of the Khepera IV in the CoppeliaSim simulator. The navigation control results show significant improvements over previous works. This is evident in both the maximum navigation speed and the hit rate of the traffic sign detection system. We also analyzed the navigation control, which achieved an average success rate of <semantics>93%</semantics>. The architecture allows testing new control techniques or algorithms based on Python, facilitating future improvements.